Nonwoven geotextiles from nettle and poly(lactic acid) fibers for slope stabilization using bioengineering approach. Issue 2 (April 2018) - Kumar, Navdeep; Das, Dipayan
Abstract: This article deals with needle-punched nonwoven geotextiles prepared from nettle and poly(lactic acid) fibers in different weight proportions for potential slope stabilization application using bioengineering approach. The geotextiles were tested for tensile strength, biodegradability, and enhancement of soil fertility. The tensile strength of the geotextiles was found to decrease with addition of stronger nettle fibers. This apparently surprising behavior was explained in the light of theoretical tensile mechanics of nonwovens. Further, the nettle fibers displayed higher biodegradability than the poly(lactic acid) fibers, and when buried under soil, all the geotextiles exhibited a loss in tensile strength. Interestingly, the fertility of the soil was remarkably improved after biodegradation of poly(lactic acid) fibers. Overall, the nonwoven geotextiles prepared in this work were found to be promising for slope stabilization application.